EVALUASI IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN MATEMATIKA SEKOLAH MENENGAH PERTAMA NEGERI DI KECAMATAN DUAMPANUA KABUPATEN PINRANG - Ismail, Nur Ikhsan; Baso Intang Sappaile; Iwan Suhardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This evaluative study aims to assess the implementation of the Independent Curriculum in mathematics learning at public junior high schools in Duampanua Subdistrict, Pinrang Regency. The research uses the CIPP evaluation model (Context, Input, Process, Product). Data collection was conducted through questionnaires and interviews with school principals, mathematics teachers, and students. The collected data were analyzed using both quantitative and qualitative descriptive methods. The study's findings indicate that: (1) the Operational Curriculum of Educational Units (KOSP) has been implemented as expected; (2) the capacity of educational units still requires improvements to fully support the optimal implementation of the Independent Curriculum; (3) the mathematics learning process meets the established criteria; (4) students' mathematics learning outcomes have shown excellent results, in line with the Criteria for the Achievement of Learning Objectives (KKTP).